2007
DOI: 10.1016/j.atmosenv.2007.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Elevated atmospheric CO2 concentration and temperature across an urban–rural transect

Abstract: The heat island effect and the high use of fossil fuels in large city centers are well documented, but by how much fossil fuel consumption is elevating atmospheric CO 2 concentrations and whether elevations in both atmospheric CO 2 and air temperature from rural to urban areas are consistently different from year to year are less well known. Our aim was to record atmospheric CO 2 concentrations, air temperature and other environmental variables in an urban area and compare it to suburban and rural sites to see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
114
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(138 citation statements)
references
References 26 publications
(39 reference statements)
8
114
1
3
Order By: Relevance
“…When integrated across the day, Vulcan mobile source emission estimates were 42.7% and 58.7% higher during the weekday compared to weekends in Boston and Worcester, respectively, which is consistent with elevated CO 2 mixing ratios observed during weekdays at each site. Observational studies in Portland and Phoenix showed weekday/weekend differences as high as 4.0 and 14.4 ppm, respectively [15,41], while a study from suburban Baltimore showed no significant weekend difference [17]. Weekend effects reflect the importance of local commuting patterns on observations of CO 2 mixing ratios.…”
Section: Trends In Observed Comentioning
confidence: 99%
See 1 more Smart Citation
“…When integrated across the day, Vulcan mobile source emission estimates were 42.7% and 58.7% higher during the weekday compared to weekends in Boston and Worcester, respectively, which is consistent with elevated CO 2 mixing ratios observed during weekdays at each site. Observational studies in Portland and Phoenix showed weekday/weekend differences as high as 4.0 and 14.4 ppm, respectively [15,41], while a study from suburban Baltimore showed no significant weekend difference [17]. Weekend effects reflect the importance of local commuting patterns on observations of CO 2 mixing ratios.…”
Section: Trends In Observed Comentioning
confidence: 99%
“…For example, CO 2 mixing ratios have been found to be higher in urban centers compared to adjacent rural locations in Phoenix [15], Salt Lake City [16], and Baltimore [17]-a phenomenon known as an "urban CO 2 dome". These higher mixing ratios are due in part to local traffic emissions, as seen in Helsinki [18], Mexico City [19], and Basel [20], but may also be effected by residential, commercial, and industrial emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring the gradient of carbon dioxide between urban and rural locations (e. g. Berry & Colls, 1990a/b;Ziska et al, 2004;George et al, 2007). All of these studies were carried out by stationary measurements.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…The consistent long-term increase in atmospheric CO 2 concentration makes it important to explore the temporal variations of atmospheric CO 2 . Meanwhile, it is also important to examine the spatial variations since atmospheric CO 2 concentration in the surface layer of the atmosphere varies significantly over different land covers (George et al, 2007;Zhang et al, 2008;Jacobson, 2010), although CO 2 is generally assumed to be wellmixed in the boundary layer. Better knowledge of the temporal and spatial variations of CO 2 concentration in the surface layer of the atmosphere is needed to improve the forecast of future CO 2 concentration levels (Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%